Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1017/s1068280500000022
|View full text |Cite
|
Sign up to set email alerts
|

Seafood Safety Perceptions and Their Effects on Anticipated Consumption under Varying Information Treatments

Abstract: This paper identifies factors that influence consumers' seafood safety perceptions and examines how these perceptions affect consumers' anticipated consumption when consumers are provided with additional information relevant to seafood. A recursive system of equations is specified describing consumers' safety perceptions as a function of past experience with seafood, recreational harvest activities, and risk-taking behavior, and describing the influence of safety perceptions on consumers' anticipated demand re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…These influential factors include: 1) illness associated with previous consumption; 2) exposure to negative publicity about oysters (Wessells, Kline, & Anderson, 1996); and 3) demographics such as age and education (Lin, Milon, & Babb, 1991). According to previous studies, consumers believe they are able to identify safe sea mussels; however, they are willing to pay a high premium for information certifying safer products in order to avoid the high risk associated with eating unsafe mussels (Brooks, 1992;Celsi, Rose, & Leigh, 1993).…”
Section: Informational Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…These influential factors include: 1) illness associated with previous consumption; 2) exposure to negative publicity about oysters (Wessells, Kline, & Anderson, 1996); and 3) demographics such as age and education (Lin, Milon, & Babb, 1991). According to previous studies, consumers believe they are able to identify safe sea mussels; however, they are willing to pay a high premium for information certifying safer products in order to avoid the high risk associated with eating unsafe mussels (Brooks, 1992;Celsi, Rose, & Leigh, 1993).…”
Section: Informational Labelingmentioning
confidence: 99%
“…According to previous studies, consumers believe they are able to identify safe sea mussels; however, they are willing to pay a high premium for information certifying safer products in order to avoid the high risk associated with eating unsafe mussels (Brooks, 1992;Celsi, Rose, & Leigh, 1993). In another study, Wessells et al (1996) found labeling greatly impacts the food choices of those who were unconfident in their knowledge about the safety of seafood.…”
Section: Informational Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, policy makers have reinforced controls and strengthened the role of food safety agencies. Partly due to these changes, many authors in recent years have started to analyse consumers' increasing concerns about food safety and its effect on food choices (Wessells et al, 1996;Cowan, 1998;Verbeke andViaene, 1999, 2001;Porin and Mainsant, 1998;Henson and Northen, 2000, among others).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have designed "ad hoc" surveys to evaluate to what extent consumers took into account food safety issues when making food choices (Wessells et al, 1996;Cowan, 1998;Verbeke andViaene, 1999, 2001;Porin and Mainsant, 1998;Henson and Northen, 2000, among others).…”
Section: Introductionmentioning
confidence: 99%